Learning curve in laparoscopic hysterectomy: yuva experience - Anshu Sharma; Priyanka Chaudhary; Prachi Singhal; Rajiv Acharya; Alok Sharma; Vineeta Gupta; Bhawna Sharma (Barpeta Obstetrics and Gynaecological Society, 2020)
Objective: To evaluate the learning process for laparoscopic hysterectomy (LH) among yuva surgeons. Material and methods: A retrospective comparative study was conducted of all laparoscopic hysterectomies by yuva surgeons (<40years) at Shri Guru Ram Rai Medical college, Dehradun. All the cases of laparoscopic hysterectomy from April 2016 to March 2018 were included in the study. The cases done from April 2016 to November 2016 were categorised in group A, from December 2016 to July 2017 were categorised in group B and from August 2017 to March 2018 were categorised in group C. Various parameters including number of cases, time period, laparotomy conversion, complications and duration of hospital stay were studied. Results: Laparoscopic hysterectomy was performed in 92 patients, out of which 16 cases were in group A, 31 in group B and 45 cases in group C. The mean duration of the operation was 160 minutes in group A,124 minutes in group B and 140 minutes in group C. Average length of hospital stay was 5 days in group A and 4 days in group B and C. The reason for converting to laparotomy in 17 cases (6 in group A, 7 in group B and 4 in group C) was achieving hemostasis (in 7 cases), dense adhesion due to endometriosis ( in 4 cases) and obliteration the pouch of Douglous by large myoma (in 6 cases). Ureteric injury occurred in 2 cases (1 case managed intraoperatively another diagnosed after a fortnight and managed thereafter). Bladder injury detected and managed intraoperatively in one case. Conclusion: Minimal invasive surgery has been accepted as a new appropriate option, replacing open surgical technique in almost all surgical disciplines. To reach to an optimal level of surgical skill adequate training, number of cases and time is required. However, route of surgery should be judiciously decided after careful case selection.